2021
DOI: 10.1038/s41419-021-04408-x
|View full text |Cite
|
Sign up to set email alerts
|

PACS-2 attenuates diabetic kidney disease via the enhancement of mitochondria-associated endoplasmic reticulum membrane formation

Abstract: The altered homeostasis of mitochondria-associated endoplasmic reticulum (ER) membranes (MAM) was closely associated with the pathological process of nervous system diseases and insulin resistance. Here, the exact implication of phosphofurin acidic cluster sorting protein 2 (PCAS-2), an anchor protein in the MAM interface, in diabetic kidney disease was investigated. In the kidneys of type 1 and type 2 diabetes mice and HG-induced HK-2 cells, a notable disruption of ER-mitochondria interactions, accompanied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…Among them, in order to verify the quality of rat liver MAM fractions, we performed quality control on different steps of MAM preparation of ZL rat livers ( n = 3) by western blot analysis ( Supplementary Figure S1 ). The distribution trend of six molecules, such as MAM labeled acyl-CoA synthase long chain 4 (ACSL4/FACL4) in different fractions was consistent with the previously published data ( Sonn et al, 2021 ; Xue et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Among them, in order to verify the quality of rat liver MAM fractions, we performed quality control on different steps of MAM preparation of ZL rat livers ( n = 3) by western blot analysis ( Supplementary Figure S1 ). The distribution trend of six molecules, such as MAM labeled acyl-CoA synthase long chain 4 (ACSL4/FACL4) in different fractions was consistent with the previously published data ( Sonn et al, 2021 ; Xue et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, the overexpression of PACS‐2 effectively shielded diabetic kidneys and high glucose‐treated HK‐2 cells from tubular damage. These findings highlight a crucial role for PACS‐2 in the progression of diabetic kidney tubular injury, via stabilization of the MAM (Xue et al, 2021). Now such cross‐organelle stress response can be evaluated by using computational analysis of RNAi signals.…”
Section: Mitochondria‐er Crosstalk During Kidney Diseasesmentioning
confidence: 77%
“…These findings highlight a crucial role for PACS-2 in the progression of diabetic kidney tubular injury, via stabilization of the MAM (Xue et al, 2021). Now such cross-organelle stress response can be evaluated by using computational analysis of RNAi signals.…”
Section: Mitochondria-er Crosstalk During Kidney Diseasesmentioning
confidence: 91%
“…Krzysiak et al (2018) also suggested that the loss of Pacs-2 protected HFD-induced obese mice from both hepatic steatosis and whole-body adiposity by elevating liver SIRT1 activity and its downstream fatty acid oxidation genes. Besides, a recent study showed that the expression of PACS-2 decreased in the kidneys of type 1 and type 2 diabetes mice and Pacs-2 knockout mice with diabetes displayed deterioration of kidney function (Xue et al 2021). However the role of PACS-2 in tubular cells under diabetic condition remains to be further elucidated.…”
Section: Discussionmentioning
confidence: 97%